Functional reconstruction of the unilateral supraglottis and piriform sinus with a triple chimeric superficial circumflex iliac artery perforator flap after supraglottic laryngectomy: A case report. Issue 3 (15th August 2022) - Werner, Jonas; Rajan, Gunesh P.; Scaglioni, Mario F.
Abstract: Preservation of laryngeal functions after supraglottic laryngectomy depends on both the extent of surgical resection and the type of reconstruction. Any reconstructive modality faces the challenges of preserving voice and swallow function due to the complex and dynamic anatomy of the larynx. In this report, we present a case in which the entire affected unilateral supraglottis and piriform sinus were functionally reconstructed using a triple chimeric superficial circumflex iliac artery perforator (SCIP) free flap. An extended unilateral supraglottic laryngectomy and neck dissection were performed in a 78‐year‐old male patient presenting with a supraglottic cT4a cN0 cM0 laryngeal cancer. The resulting defect was reconstructed using a triple chimeric SCIP flap from the right inguinal region intended to reconstruct the different affected compartments. It was based on three perforators and consisted of a 4 cm × 3 cm fascial flap from the external oblique muscle and two fasciocutaneous paddles measuring 6 cm × 2 cm and 3 cm × 4 cm. The arterial and venous vessels were anastomosed to the superior thyroid artery and internal jugular vein. The fascial flap was used to reconstruct the aryepiglottic fold. The smaller fasciocutaneous paddle was utilized to reconstruct the affected piriform sinus and former thyroid cartilage compartment, while the larger fasciocutaneous paddle served as a monitor skin flap. The postoperative recovery was uneventful. Laryngeal functions including voice and deglutition were well‐preserved after 4 months of rehabilitation. The patient showed no signs of chronic aspiration or tumor recurrence 6 and 12 months postoperatively. The pliable and versatile triple chimeric SCIP flap provides a useful free flap option for a tailored functional reconstruction after an extended supraglottic laryngectomy. Restoration of larynx elevation and mobility with the presented technique substantially improves swallow rehabilitation while preserving the voice.